(untitled) (Vietnam Journal of Community Medicine, 2022)
Preauricular sinuses are common congenital malformations that usually occur at the anterior margin of the ascending limb of the helix. Classically, a preauricular sinus presents as a small opening, usually near the anterior to crus of helix and anterior-superior of tragus. The variant type of preauricular sinus is called postauricular sinus with location of the fistula pit positioned posterior to the imaginary tragal extended line. In fact, preauricular sinuses can also mimic epidermoid cyst or first branchial cleft fistula if pit of sinus was not clear. In this study, we reported 3 rare cases of postauricular sinus with recurrent epidermoid cyst at anterior area of tragus and swelling at intertragal notch, the small opening “pit” of the sinuses can only be identified under a microscopy and in addition, inside- out methode seemed to be a better approach to control total ramifications with squamous epithelium.